Little bat - Cox, Tania; illustrated by Andrew McLean (New York : Scholastic, 2000)
Little Bat is nervous. She's never flown before. But with a little help from her friends and a lot of encouragement from her mother, Little Bat finds that launching herself into the world is not so scary after all!
Keywords: Bat - Fiction. -- Encouragement